2019
DOI: 10.1080/19420862.2018.1564510
|View full text |Cite
|
Sign up to set email alerts
|

A recycling anti-transferrin receptor-1 monoclonal antibody as an efficient therapy for erythroleukemia through target up-regulation and antibody-dependent cytotoxic effector functions

Abstract: Targeting transferrin receptor 1 (TfR1) with monoclonal antibodies is a promising therapeutic strategy in cancer as tumor cells often overexpress TfR1 and show increased iron needs. We have re-engineered six anti-human TfR1 single-chain variable fragment (scFv) antibodies into fully human scFv 2 -Fcγ1 and IgG1 antibodies. We selected the more promising candidate (H7), based on its ability to inhibit TfR1-mediated iron-loaded transferrin internalization in Raji cells (B-cell lymphoma). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 47 publications
0
20
1
Order By: Relevance
“…The third fully human antibody that has been developed is the H7 neutralizing IgG1 antibody (H7-IgG1) for which the variable regions from the 3GH7 scFv described above were used to produce a human IgG1 antibody ( 175 ). Another version of this antibody was produced containing two scFvs linked to the Fc region of human IgG1 (H7-Fc).…”
Section: Targeting Tfr1 For Cancer Therapymentioning
confidence: 99%
See 2 more Smart Citations
“…The third fully human antibody that has been developed is the H7 neutralizing IgG1 antibody (H7-IgG1) for which the variable regions from the 3GH7 scFv described above were used to produce a human IgG1 antibody ( 175 ). Another version of this antibody was produced containing two scFvs linked to the Fc region of human IgG1 (H7-Fc).…”
Section: Targeting Tfr1 For Cancer Therapymentioning
confidence: 99%
“…Interestingly, only the H7-Fc was able to bind human and mouse TfR1, while the full length H7-IgG1 antibody was only able to bind human TfR1. Both forms of the H7 antibody inhibited the in vitro growth and induced apoptosis in human ERY-1 erythroleukemia cells, and human Raji BL cells ( 175 ). Both formats also induced ADCC activity, but the H7-IgG1 showed more potent ADCC activity ( 175 ).…”
Section: Targeting Tfr1 For Cancer Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have reported that TFR1 is involved in kinds of diseases, including cancers, anaemia, and neurodegenerative diseases. Most importantly, TFR1 was verified to be abnormally expressed in various cancers, and some experimental and clinical drugs and antibodies targeting this protein have shown strong anti-tumour effects [38][39][40][41][42][43][44][45][46]; herein, TFR1 is suggested to be a potential molecular biomarker for targeted cancer diagnosis and therapy. SAHH, encoded by the AHCY gene, belongs to the adenosylhomocysteinase family and is a competitive inhibitor of S-adenosyl-L-methionine-dependent methyltransferase reactions and might play a key role in the control of methylation by regulating the intracellular concentration of adenosylhomocysteine.…”
Section: Discussionmentioning
confidence: 99%
“…In single chain variable fragment (scFV) small peptide linker connects the VH and VL chain. When an antibody against anti-transferrin receptor-1 (TfR1) was re-engineered from anti-human TfR1 single-chain variable fragment (scFv) antibodies into fully human scFV2-Fcγ1 and IgG1 antibodies; it resulted in a better candidate of antibody therapy for leukemia and lymphoma [48].…”
Section: Monoclonal Antibody For Leukemia Treatmentmentioning
confidence: 99%